Navigating complexity: a systematic review of the challenges in Community-Based Rehabilitation (CBR) implementation - Yaakub, Farhana; Kassim, Asiyah; Tumin, Makmor (Faculty of Administrative Science and Policy Studies, 2025)
Community-Based Rehabilitation (CBR) Program is a global effort proposed by the World Health Organization (WHO) to cater the needs of people with disabilities (PWDs). As the number of registered PWDs increases annually, the demand for accessible rehabilitation services becomes more urgent to foster their social inclusion. While the government and community are focusing on providing better and reachable rehabilitation services based on the local capacities and resources, they face multiple challenges in the implementation program. This study aims to systematically review and synthesize the challenges of CBR implementation. Following the PRISMA guidelines, 13 eligible studies were selected and critically appraised by using CASP Checklist and then analysed using thematic analysis to identify recurring themes. From the analysis, five main themes are highlighted: 1. lack of skilled workforce and training deficiencies; 2. insufficient resources; 3. poor integration and coordination; 4. attitudinal and cultural barriers; 5. barriers to accessing CBR services. To reap its great potential in empowering PWDs, CBR must be backed by strong and coordinated policies, well trained manpower, sustainable funding, and social support.